Advanced approaches for endotoxin detection and removal from snake antivenoms. (15th January 2023) - Sheraba, Norhan S.; Hesham, Ahmed; Fawzy, Mohamed; Diab, Emad; Basuony, Mohamad E.; Yassin, Aymen S.; Zedan, Hamdallah H.; Abu-Elghait, Mohammed
Abstract: A comprehensive assessment of the literature on strategies for the detection and removing endotoxin from biotechnological preparations was conducted. This study highlighted the brief history of endotoxin. After that, a review of endotoxin's chemical and physical features, as well as its pathophysiological consequences when the body is exposed to LPS excessively or systemically, is presented. The procedures for determining endotoxin and the interaction of endotoxin with proteins are also discussed, considering both known approaches and cutting-edge technology in this sector. This review presented the endotoxin detection and removal approaches from antisera with an economical approach using several processes documented in the literature (e.g., adsorption, ultrafiltration, and chromatography). Different methods with relatively high protein recoveries are mentioned. This review concludes that heat activation at 70 °C–80 °C for 10 min and rehydration of the LAL reagent with endotoxin-specific buffer solution is the best technique to control the enhancement problem when testing polyvalent snake venom antiserum samples by the LAL method. The most efficient method for eliminating endotoxins has proven to be affinity resin-based chromatography. Graphical abstract: Image 1 Highlights: Affinity resin-based chromatography has the most effective approach for removing endotoxins. Molecular filtration may be useful for eliminating bacterial lipopolysaccharide from non-protein solutions. Efficient dehydrogenation techniques must be developed for endotoxin-free product.